A review energy-efficient task scheduling algorithms in cloud computing - Atiewi S.; Yussof S.; Ezanee M.; Almiani M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Algorithms; Energy efficiency; Internet protocols; Multitasking; Network management; Scheduling; Scheduling algorithms; Datacenter; DVFS; Energy efficient; GreenCloud; Task-scheduling; Virtual machines; Virtualizations; Cloud computing